Cardiac lymphoma in dogs – - Natália Pisciottano Noronha (Brazilian Journal of Veterinary Research and Animal Science, 2019)
Lymphoma is a very common lymphoid malignancy in dogs, but cardiac involvement is rare. Primary cardiac lymphoma is defined as lymphoma involving the heart, the pericardium, or both, and is classified as extranodal anatomical form. The present report describes the cases of three animals with cardiac lymphoma. All cases presented moderate to severe pericardial effusion and cardiac tamponade. The cytological analysis of the effusion was consistent with the diagnosis of cardiac lymphoma. The anatomopathological evaluation of the tumor extracted from the heart of one of the animals, after euthanasia, was consistent with cardiac lymphoma. The other two animals were treated with Madison-Wisconsin chemotherapy protocol and survived between 6 to 8 months. This report emphasizes the importance of pericardial effusion cytology for the diagnosis, appropriate treatment approach and monitoring of cardiac tumors in dogs and cats.